Investigation of the efficacy and safety of cryoablation and intra-arterial PD-1 inhibitor in patients with advanced disease not responding to checkpoint inhibitors: An exploratory study - Wei, Fuqun; Guo, Rui; Yan, Yuan; Lin, Ruixiang; Chen, Jin; Lin, Zhengyu (Frontiers in Immunology, 2022)
Objective: To explore the effectiveness of cryoablation in overcoming immune resistance in advanced solid cancers. Methods: In this pilot study, nine solid cancer patients were treated with tumour cryoablation and arterial perfusion with programmed cell death protein 1 inhibitors previously proven ineffective. The CIBERSORT software was used to estimate the levels of tumour-infiltrating immune cells in the challenged tumours. Changes in circulating T cells were assessed using flow cytometry. Primary endpoints were the disease control and objective response rates, and the secondary endpoint was safety. Results: Nine patients with advanced solid tumours received cryoablation between June and December 2021. The median follow-up time was 5.8 months. We recorded an objective response rate in two patients (22.22%). The best overall responses were two partial responses (22.22%), one case (11.11%) of stable disease, and six patients (66.67%) presented progressive disease. However, the median overall survival time was not reached. The median progression-free survival was 2.4 months. Treatment-related severe adverse events included one case of abdominal infection and one case of upper gastrointestinal bleeding, which were cured after the intervention. The CIBERSORT software proved the importance of cryoablation in regulating tumour-infiltrating immune cells. Macrophages were polarised from M2 to M1. A gradual increase in CD4+ T cells was observed after the administration of the combination therapy. Conclusion: Cryoablation has the potential to overcome immune resistance effectively and safely in patients with advanced solid cancers. Cryoablation polarises macrophages from M2 to M1 to enhance antitumour immunity.